PELATIHAN PEMBUATAN DESAIN GRAFIS MULTIMEDIA INTERAKTIF DI SMA NEGERI 13 PALEMBANG - Tandoballa, Lucky; Wahyuni, Sri; Agustria, Kevin; Hartati, M. Kom, Ery (Politeknik Negeri Sriwijaya, 2024)
Most importance of digital technology in the 4.0 era and 5.0 society, with a focus on the graphic design profession, which works with various visual media such as illustration, typography, photography, animation and video to create creative works such as brochures and advertisements. Presenting interesting and informative information through infographics is key to conveying messages to readers using apps like Canva. Canva, founded in 2012 by Melanie Perkins, is an online graphic design tool that allows users to easily create and edit designs. The use of Canva in the world of education, such as at SMA Negeri 13 Palembang, helps students understand how to use technology for various purposes, including learning, business, and creating personal biodata. Canva's main features include many available templates, although some of them cost money and require Internet support. This community service activity is effective in introducing and teaching the use of Canva to create presentations, posters, animations and personal biodata. The event ended with a group photo session, and the participants hoped that a similar program would be held again to deepen their understanding of Canva features.